2014
DOI: 10.1142/s0192415x14500529
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Stress Urinary Incontinence by Ginsenoside Rh2

Abstract: Stress urinary incontinence (SUI) is a common disorder in middle-aged women and the elderly. Although surgical treatment of SUI has progressed, there are no effective pharmacological therapies without a side effect. We studied the effect of ginsenoside Rh2 against SUI. Here, we studied the effect of ginsenoside Rh2 on the contractile force of the urethra and blood vessels in an ex vivo organ bath assay. We further investigated the mechanisms and effects of Rh2 in cell culture and animal models. Ginsenoside Rh2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The peak bladder pressure was taken as the LPP. At least 3 LPPs were obtained for each animal, and the mean LPP was calculated [24, 25]. …”
Section: Methodsmentioning
confidence: 99%
“…The peak bladder pressure was taken as the LPP. At least 3 LPPs were obtained for each animal, and the mean LPP was calculated [24, 25]. …”
Section: Methodsmentioning
confidence: 99%
“…VD is used to induce SUI in mice and rats, as evidenced by LPP and/or maximal urethral closing pressure (MUCP) on urodynamic testing [1, 8, 21, 22]. An SUI mouse model revealed that a 0.3-ml intravaginal balloon (diameter ∼8 mm, equal to brain-case diameter of newborn mice) produced greater LPP than 0.1- and 0.2-ml balloons [23].…”
Section: Discussionmentioning
confidence: 99%
“…The peak bladder pressure was taken as the LPP. At least three LPPs were obtained for each animal, and the mean LPP was calculated [43] , [44] .…”
Section: Methodsmentioning
confidence: 99%